Disease pattern in patients presenting to a primary health center near Kathmandu, Nepal - Ansari, Shaheen (Journal of Patan Academy of Health Sciences, 2015)
Introductions: Audits from bigger hospitals are common place, but reports from smaller institutions like PHC’s are rarely published. This study was done to find the demographic attributes of patients presenting to Khopasi primary health center and to analyze the disease pattern of patients. Methods: This was a cross sectional study conducted at Khopasi PHC over six months between October 2012 to March 2013. The data was collected from the register kept in the OPD. Those with incomplete entries were excluded. Simple statistical methods like means and percentages were used to analyze the data. Results: Total number of patients presenting to the out-patient department in the study period was 3,108 of which 1,196 (62%) were females. Most patients 567 (18%) were from 5-14 years age group. Respiratory Tract Infection was the most common cause 489 (16%) for these consultations. It was closely followed by Ear Nose Throat infections 415 (13%) and Acid Peptic Disease 367 (11%). Among children of <5 years, 270 (62%) were found to have acute respiratory infections. Conclusions: Most patients were young female. Infectious diseases of respiratory tract and Ear Nose Throat were more than one-third of the consultations. Journal of Patan Academy of Health Sciences. 2014 Dec;1(2):64-66